2020
DOI: 10.1097/j.jcrs.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Visual function and subjective perception of vision after bilateral implantation of monofocal and multifocal IOLs: a randomized controlled trial

Abstract: Following implantation with Multifocal intraocular lenses (MIOLs) or monofocal intraocular lenses (IOLs), the study examines monocular and binocular visual function and patient reporting outcomes using a rigorous series of clinical assessments. Setting: BMI Southend Hospital, UK DESIGN: Prospective, randomised, double-masked clinical trial. METHODS: 100 subjects were randomised for bilateral implantation of either Bi-Flex 677MY MIOL or Bi-Flex 677AB IOL and were assessed at 3-6 months (V1) and 12-18 months (V2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
7
2
Order By: Relevance
“…Because all surgeries were performed by the same experienced surgeon using the same surgical protocol with the utmost caution, we believe that the differences in frequency and severity of PCO are likely explained by differences in IOL design [16,46]. We acknowledge that our reported 1-year rates for PCO and Nd:YAG capsulotomy are higher than those reported in other studies [29,[47][48][49]. The definition of PCO and the criteria for performing Nd:YAG capsulotomy, however, may differ between centers.…”
Section: Discussionmentioning
confidence: 86%
“…Because all surgeries were performed by the same experienced surgeon using the same surgical protocol with the utmost caution, we believe that the differences in frequency and severity of PCO are likely explained by differences in IOL design [16,46]. We acknowledge that our reported 1-year rates for PCO and Nd:YAG capsulotomy are higher than those reported in other studies [29,[47][48][49]. The definition of PCO and the criteria for performing Nd:YAG capsulotomy, however, may differ between centers.…”
Section: Discussionmentioning
confidence: 86%
“…However, disturbing photic phenomena, such as glare and haloes, are some of the main complaints in patients who have undergone multifocal IOL implantation, influencing their daily quality of life and overall satisfaction with the surgery. 1,2 Previous studies have shown that abnormal deviations between the optical axis and the visual axis (angle a) or between the pupillary axis and the visual axis (angle k) can lead to increased higher-order aberrations and consequent photic phenomena, causing impaired visual quality in patients after multifocal IOL implantation. [3][4][5] Therefore, angle k and angle a have been gradually taken into consideration in the surgical planning of functional IOLs.…”
mentioning
confidence: 99%
“…However, disturbing photic phenomena, such as glare and haloes, are some of the main complaints in patients who have undergone multifocal IOL implantation, influencing their daily quality of life and overall satisfaction with the surgery. 1,2…”
mentioning
confidence: 99%
“…For instance, spectacle independence at near has been reported for the 677MY to be between 75% and 100% and between 93% and 100% for intermediate, but these percentages were not collected with the PRSIQ. 10,11,21…”
Section: Discussionmentioning
confidence: 99%
“…6 Clinical results with the EPS technology have been widely reported for the Liberty 677MY (EPS 1.0), but a new optimized EPS version for increasing light intensity distribution at intermediate distance has been designed (EPS 2.0), decreasing far and near light intensity, in such a low degree, that this optimization could have a clinically negligible decrease on far and near distance visual acuities but a clinically relevant increase at intermediate visual acuity (VA). [7][8][9][10][11] The aim of this study was to evaluate the safety, predictability, and efficacy of the implantation of a mIOL with this optimized EPS. The secondary aim was to assess the defocus curves (DCs) and patient-reported outcomes at 1 year postoperatively.…”
mentioning
confidence: 99%